Recognizing Genuine From Posed Facial Expressions: Exploring the Role of Dynamic Information and Face Familiarity - Lander, Karen; Butcher, Natalie L. (Frontiers in Psychology, 2020)
The accurate recognition of emotion is important for interpersonal interaction and when navigating our social world. However not all facial displays reflect the emotional experience currently being felt by the expresser. Indeed faces express both genuine and posed displays of emotion. In this article, we summarise the importance of motion for the recognition of face identity before critically outlining the role of dynamic information in determining facial expressions and distinguishing between genuine and posed expressions of emotion. We propose that both dynamic information and face familiarity may modulate our ability to determine whether an expression is genuine or not. Finally, we consider the shared role for dynamic information across different face recognition tasks and the wider impact of face familiarity on determining genuine from posed expressions during real-world interactions.